Music: A Very Short Introduction - Cook, Nicholas (Oxford Oxford University Press, 1998)
What is music? How is it constructed? How is it consumed? Why do you enjoy it at all? In Music: A Very Short plays Introduction, Nicholas Cook invites us to really think about music and the role it plays in our lives and our ears. Drawing on a number of accessible examples, the author prompts us to call on our own musical experiences in order to think more critically about the roles of the performers and the listener, about music as a commodity and an experience, what it means to understand music, and the values we ascribe to it.This very short introduction, written with both humor and flair, begins with a sampling of music as human activity and then goes on to consider the slippery phenomenon of how music has become an object of thought. Covering not only Western and classical music, Cook touches on all types from rock to Indonesian music and beyond. Incorporating musical forms from every continent, Music will make enjoyable reading for beginner and expert alike.
Keywords: Music philosophy and esthetics; Gender